2016
DOI: 10.1371/journal.pone.0153059
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 Accelerates Mortality by Promoting the Progression of the Systemic Lupus Erythematosus-Like Disease of BXSB.Yaa Mice

Abstract: IL6 is a multifunctional cytokine that drives terminal B cell differentiation and secretion of immunoglobulins. IL6 also cooperates with IL21 to promote differentiation of CD4+ T follicular helper cells (TFH). Elevated serum levels of IL6 correlate with disease flares in patients with systemic lupus erythematosus (SLE). We previously reported that IL21 produced by TFH plays a critical role in the development of the SLE-like disease of BXSB.Yaa mice. To examine the possible contributions of IL6 to disease, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 57 publications
3
15
1
Order By: Relevance
“…Several elements of the immune system are potential targets for therapeutic intervention in patients with SLE. In this sense, IL‐6 is implicated in the development and progression of SLE in mice and it is identified as one of the major genetic risk factors for SLE in humans ; thus, its modulation seems to be a potential therapeutic approach in SLE management . In the present study, we found a remarkable increase of IL‐6 production in patients with SLE compared with healthy subjects.…”
Section: Discussionsupporting
confidence: 63%
“…Several elements of the immune system are potential targets for therapeutic intervention in patients with SLE. In this sense, IL‐6 is implicated in the development and progression of SLE in mice and it is identified as one of the major genetic risk factors for SLE in humans ; thus, its modulation seems to be a potential therapeutic approach in SLE management . In the present study, we found a remarkable increase of IL‐6 production in patients with SLE compared with healthy subjects.…”
Section: Discussionsupporting
confidence: 63%
“…43,44 In a lupus mouse model, IL-6 deficiency prevented T follicular helper cell differentiation and germinal-center B-cell expansion, resulting in reduced autoantibody production. 45 The present study clarified that TLR9 activation by CpG-ODN enhanced IL-6 production in splenocytes of murine IgAN. IL-6 induced overproduction of aberrantly glycosylated IgA and IgG-IgA IC in a murine model of IgAN.…”
Section: Discussionsupporting
confidence: 49%
“…Although an absolute requirement for IL-6 in T FH cell generation is controversial 131,139141 , IL-6 is known to promote early T FH cell differentiation by transiently inducing B cell lymphoma 6 (BCL-6) expression in CD4 + T cells binding cognate antigen 142 . In addition, Il6 deletion reduces disease severity in the BXSB- Yaa mouse lupus model, and increased serum IL-6 levels have been observed in human SLE, which suggests potential roles for this cytokine in disease pathogenesis 143,144 . Consistent with this idea, IL-6 receptor blockade with tocilizumab decreased the levels of dsDNA-specific antibodies and circulating plasmablasts in early-stage clinical trials in patients with SLE 145 .…”
Section: Receptor Crosstalk Shapes B Cell Activationmentioning
confidence: 99%